German yearbook of international law. - Giegerich, Thomas; Proelss, Alexander; Delbrück, Jost; Houghton, Katherine (German Yearbook of International Law / Jahrbuch für Internationales Recht., 2011)
The German Yearbook of International Law, founded as the Jahrbuch für Internationales Recht, provides an annual report on new developments in international law and is edited by the Walther Schücking Institute for International Law at the University of Kiel. Since its inception in 1948, the Yearbook has endeavored to make a significant academic contribution to the ongoing development of international law. Over many decades the Yearbook has moved beyond its origins as a forum for German scholars to publish their research and has become a highly-regarded international forum for innovative scholar.